Nicholas Rockwell. Thebes: A History - Gartland, Samuel (Journal of Greek Archaeology, 2018)
This short overview of the history of Thebes between 1600 BC and AD 476 is part of the Routledge Cities of the Ancient World series, at present a scattergun collection of studies with Elis the only other mainland Greek community published to date. It is markedly shorter than other books in the series (149 pages of text compared to 239 pages for Elis), and the claims of the book to give an up to date assessment of all available information for the city over two millennia are very difficult to meet in this length.